The Prediction of Learned Resourcefulness of High School Students by the Relationship within Their Families - Yemliha COSKUN (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
In this research, it is aimed to determine the prediction of learned resourcefulness ofhigh school students by the relationships within their families. Besides, it is inquiredwhether the learned resourcefulness level of high school students differentiateaccording to the healthiness of family functions. The population comprises all thestudents in 10th and 11th classes of private and state schools in the Anatolian side ofĐstanbul during 2006-2007 school year. Using random sampling method, 12 schools (6public, 6 private schools) were selected for the study. 738 students from these schoolswere chosen randomly. 357 of them were females, 381 of them were males. In thissurvey study, ‘personal information form’ developed by the researcher to collect dataabout socio-demographic features of students, ‘Rosembaum’s Learned ResourcefulnessScale’, and ‘McMaster Family Assessment Device’ were used to collect data. Theresults of this study show that relationship within family predicts learnedresourcefulness of the students significantly. Also, the learned resourcefulness scoresof the students with healthy family functions are higher than the students withunhealthy family functions.